Narratives of labour in the past - Endreva, Maria (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2022)
The article traces the different narratives around labour, from the Christian stories about it to its integration into ideologies of nationalism and fascism. It showcases the medieval understanding of work as punishment for a committed sin, the first positive indicators of labour as a means of ethical education during the Reformation, and their development during the Enlightenment. Romanticism opposes those ideas through its glorification of idleness, but in the rise of capitalism labour becomes a pillar of working class ideologies in the 19th and early 20th centuries.
Keywords: labour; narrative; relations of power; disciplinary society